2019
DOI: 10.1097/phm.0000000000001277
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation on Motor Recovery for Patients With Stroke

Abstract: Objective A systematic review and meta-analysis were conducted to determine the efficacy of repetitive transcranial magnetic stimulation in recovering motor function in patients with stroke. Design A comprehensive literature search was performed to identify studies published before September 20, 2018. Electronic databases were searched. Standard mean differences and 95% confidence intervals were used to evaluate the effects of repetitive transcranial ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 37 publications
1
27
1
Order By: Relevance
“…In contrast to our results, several studies have reported the positive short-and long-term effectiveness of rTMS treatment on recovery of motor function after stroke (Chang et al, 2010;He et al, 2019;Nam et al, 2018;Noh et al, 2019;Ueda et al, 2019). Previous studies proposed that increased excitability of the affected hemisphere by rTMS treatment improves motor function by facilitating corticomotor excitability (Khedr et al, 2010;Kim et al, 2006;Wassermann, 1998).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, several studies have reported the positive short-and long-term effectiveness of rTMS treatment on recovery of motor function after stroke (Chang et al, 2010;He et al, 2019;Nam et al, 2018;Noh et al, 2019;Ueda et al, 2019). Previous studies proposed that increased excitability of the affected hemisphere by rTMS treatment improves motor function by facilitating corticomotor excitability (Khedr et al, 2010;Kim et al, 2006;Wassermann, 1998).…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have reported that neurostimulation enhances motor outcome after stroke; however, this is still the subject of debate (Chang et al, 2010;Hao et al, 2013;He et al, 2019;Simis et al, 2016). Many previous studies have limitations in that they did not adjust for critical factors that can affect the motor outcome, including the location of the stroke lesion and the state of motor function-related neural tracts.…”
Section: Introductionmentioning
confidence: 99%
“…However, further studies need to be performed to confirm the validity and investigate the mechanisms of these stategies (7,8). As a novel neuro-manipulated technique, rTMS has been widely used across a range of altered states including neurological and psychiatric conditions, especially popular in treating Alzheimer's disease (AD), mild cognitive impairment (MCI), depression, mental disease, and stroke with physical disorder, aphasia or dysphagia (9)(10)(11)(12)(13)(14)(15). The advantages of rTMS are non-invasively and painlessly modulating the cortical excitability (excite or inhibit) of both the stimulated region and some distant regions in the brain (16), and reorganizing functional connectivity among certain regions to ameliorate brain networks (17).…”
Section: Introductionmentioning
confidence: 99%
“…For example, cerebral inflammation and angiogenesis are two of multiple overlapping processes between glioma surgery and cerebral ischemic stroke pathways [36]. A recent meta-analysis on 841 patients across 20 randomized controlled trials (RCTs) demonstrates that rTMS is beneficial to the treatment of post-stroke hemiplegia, especially in: lower limb functioning, grip strength, and attenuating stroke severity [15]. Interestingly, cortical reorganization can be observed between primary motor and secondary motor cortices in stroke patients to facilitate improved motor functioning, leading authors to suggest the need for future customized TMS applications based on the newly activated cortical pathways in these stroke patients [37].…”
Section: Rtms Therapy For Stroke and Surgerymentioning
confidence: 99%
“…While meta-analyses highlight the remarkable safety of rTMS in ischemic stroke patients with extremely low-risks for seizures [15,16], there remains limited descriptions on the safety and efficacy of this treatment modality in tumor patients in the acute post-operative period. Given the striking advances in fields outside neuro-oncology, individualised TMS therapy merits investigation to accelerate recovery trajectories post-craniotomy.…”
Section: Introductionmentioning
confidence: 99%